CHRONIC THROMBOEMBOLIC PULMONARY HYPERTENSION AND PROBLEMS OF RARE AND INTERDISCIPLINARY DISEASE - N. A. Shostak (Racionalʹnaâ Farmakoterapiâ v Kardiologii, 2015)
Chronic thromboembolic pulmonary hypertension (CTEPH) is a rare life-threatening disease with a prevalence of 2 cases per 100000 population. CTEPH is a chronic, progressive disease characterized by high disability and mortality rates in young and middle-aged people, often with underlying genetic and autoimmune thrombophilic disorders. The need for pathogenetic therapy with orphan drugs that can slow the progression of the disease is supported.